Victor Ramos is a leading figure in General and Family Medicine in Portugal (Portuguese Journal of Family Medicine and General Practice, 2026)
In Portugal, Victor Ramos is an iconic figure in general and family medicine (GFM), known not only for his dedication as a family physician but also for his role in medical education, professional activism, and involvement in health policy. He is a unique individual who harmoniously combines human qualities—such as deep empathy—with outstanding intellectual and professional skills. His professional career runs parallel to the history of GFM and reflects a balance between a cultured, visionary spirit and a sensitive, caring personality that has always shaped his interpersonal relationships and clinical practice. He anticipated needs and opportunities within the health system and translated ideas into concrete projects, achieving tangible results such as the implementation of the primary health care (PHC) reform and the creation of Family Health Units (FHU). For these reasons, he is widely recognized for his ability to bring together a broad, strategic, and pragmatic vision, which has enabled him to influence significant changes in healthcare in Portugal.
Keywords: Legacy; General medicine; Family medicine